Semiotika Pemasaran Sanggar Seni Kinanti Sekar Yogyakarta - Widharta, Elyandra (Universitas Negeri Surabaya, 2024)
This research discusses the marketing seminars of Kinanti Sekar Art Studio in Yogyakarta. Apparently the art studio is currently using a digital promotion strategy. So in its management, it uses creative ways by producing sign systems in the form of logos, symbols, messages, colors, texts, and meanings in its marketing semiotics. This research uses a qualitative method with interviews and direct observation with sources. The resource persons are the founders of Kinanti Sekar art studio, Kinanti Sekar Rahina as an artist and trainer of the studio and Bagas Arga Santosa as Program Coordinator of the studio. All discussion results are described in a descriptive analysis of all data that has been obtained. The results show that the promotional strategy using digital media seems to be quite effective because it is right on target and reaches the marketing target. Keywords: semiotics, marketing, art studio, kinanti sekar, dance.